BRACU new campus development project construction schedule (January.2021-March.2021) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the construction schedule from January, 2021 to March, 2021 of BRACU new campus project.